(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to the explanation of some examples of embroidery, which is considered a unique masterpiece of traditional textiles in the history of the Uzbek people, located in the museums of the world and our country. Particularly important are the sources in the embroidery of the Nurata oasis, quilted blankets, and suzani, not only in our republic but also stored in museums of foreign countries, which have captured our times and are still popular.